(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: The aims of this study to assess the practice of preventing cervical cancer of 15 - 49 years old and having gynecological examination women at Lam Dong General Hospital. Research method: A cross-sectional description. Interviewed practice about cervical cancer prevention of 400 women. Results: Over the course of the study, 400 women showed the number of women who had not been vaccinated is still high at 85.5%, the rate who had not been screened for cervical cancer is 62.3%. Based on the results of the study, we recommend that reproductive age women should be communicated more frequently about HPV vaccination and periodic cervical cancer screening to prevent cervical cancer.